Revitalizing the Local Economy: Community Empowerment through Tempe Production and Branding in Mayang District - Qoidul Khoir (PT Agung Media Publisher, 2024)
This research identifies the potential of tempe as a traditional food product in Mayang District, which is hindered by suboptimal production quality and branding. The aim of this research is to enhance the economic empowerment of the community by improving the tempe production process, developing innovative packaging, and strengthening product branding. Using a Community-Based Research (CBR) approach, this study involves technical training and branding strategy development, as well as impact evaluation through interviews, observations, and surveys. The research results show that improvements in the production process enhance the consistency of tempe, while new packaging and strengthened branding successfully attract consumer attention and boost sales. In conclusion, this program is effective in enhancing the competitiveness of tempe and empowering local communities, as well as offering a model that can be applied for the development of local products in other regions.